PENGARUH MOTIVATION, CAREER PLANNING, DAN ORGANIZATIONAL SUPPORT TERHADAP JOB PERFORMANCE MELALUI JOB SATISFACTION PADA INDUSTRI PLASTIK GRESIK - Nevi Chania Dwi Ariyanti (Jurnal Manajerial Bisnis, 2023)
This study aims to analyze the effect of Motivation, Career Planning, and Organizational Support on Job Performance through Job Satisfaction. The data analysis technique to answer the research hypothesis is path analysis. Data analysis was performed using statistics with the SmartPLS version 3.0 tool. The results showed that: (1) Motivation had no significant effect on Job Satisfaction; (2) Career Planning has no significant effect on Job Satisfaction; (3) Organizational Support has a significant effect on Job Satisfaction; (4) Motivation has a significant effect on Job Performance; (5) Career Planning has a significant effect on Job Performance; (6) Organizational Support has a significant effect on Job Performance; (7) Job Satisfaction has no significant effect on Job Performance; (8) Motivation has no significant effect on Job Performance through Job Satisfaction; (9) Career Planning has no significant effect on Job Performance through Job Satisfaction; and (10) Organizational Support has no significant effect on Job Performance through Job Satisfaction.